West Bengal Five Year Plan-A Summary (Second Edition) - Planning Commission (Planning Commission, 1955)
There never was a story without its background, and the account of the efforts of a people and their Government to improve their condition is no exception to this rule. Various reasons make this background particularly important in obtaining a true perspective of the plans of development in operation in the State of West Bengal. The war, famine, outbursts of communal frenzy, inter-district shifts of population in panic, enormous loss of territory at partition with the residue left in three disjointed portions, massive and uncontrollable movements of the dispossessed and displaced across the newly determined boundaries,—any one of these events would be a major catastrophe in the history of a people. The inhabitants of this region have suffered all of them in quick succession within the last twelve years. It is essential to bear this in mind in any attempt to understand what goes on here.
West Bengal, Development Department